2020
DOI: 10.29252/jarums.19.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Free Living Amoeba Acanthamoeba in the Nasal and Oral Discharges of HIV + / HIV­ Sample in Arak

Abstract: Background & objectives: Impaired immune system provides favorable conditions for colonization by Acanthamoeba in the human body. In this case control study, we compared the molecular and culture methods in identifying Acanthamoeba in the nasal and oral secretions of HIV + /HIVhuman. Methods: In a current case control study, nasal and oral discharge of 53, HIV + patients and 53, HIVpeople were evaluated. The nasal and oral secretions of each patient were prepared by sterile swabs and transferred to the laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Their study showed, out of 53 HIV+ patients 11 samples were positive with Acanthamoeba, and in HIV-participants 3 positive samples have been found. 30 A. lenticulata which is isolated from the majority of our positive cases is indicating its ability to colonize immunosuppressed patients.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Their study showed, out of 53 HIV+ patients 11 samples were positive with Acanthamoeba, and in HIV-participants 3 positive samples have been found. 30 A. lenticulata which is isolated from the majority of our positive cases is indicating its ability to colonize immunosuppressed patients.…”
Section: Discussionmentioning
confidence: 65%
“…In another study, researchers compared identifying Acanthamoeba in the nasal and oral samples of HIV+/HIV‐ humans. Their study showed, out of 53 HIV+ patients 11 samples were positive with Acanthamoeba , and in HIV‐ participants 3 positive samples have been found 30 …”
Section: Discussionmentioning
confidence: 97%